The Development of TT-s model (Techniques and Tactics) towards a Successful Postgraduate Studies - Rosfazila Abd Rahman; Nor ‘Adha Abdul Hamid; Norfaezah Mohd Hamidin; Djhoanna S Mama (Ittishal Educational Research Journal, 2021)
Postgraduates learning experiences namely knowledge, values and contacts acquired, professional and personal values acquired and specific learning problems encountered has shown a multiple dimension. The task of evaluating the student learning experience in postgraduate education can point out to researchers and university educators’ various mismatches that would not be immediately known otherwise. With this, universities can take proactive steps to celebrate learner diversity when addressing students’ difficulties in their continuous effort to further enhance support and facilities for their postgraduate students. This study aims to identify the elements and proposed a model of Techniques and Tactics (TT-s) that need to be implemented by educators and learners in helping to create students who are able, to succeed with further establishing best practice and effective model. Therefore, two guidelines for Models of Techniques and Tactics (TT-s) relationships for effective learning is discussed. The study is quantitative in nature and employed narrative approach. The findings are synthesized and summarized by presenting a matrix discussion of specific guidelines to increase effectiveness in the best practice and process of students learning. This study aims to propose a model to address the successful postgraduates’ studies. The model will robust postgraduates’ students to succeed in their learning journey.